2022
DOI: 10.1186/s41235-022-00440-3
|View full text |Cite
|
Sign up to set email alerts
|

Detecting a familiar person behind the surgical mask: recognition without identification among masked versus sunglasses-covered faces

Abstract: Previous research has shown that even when famous people’s identities cannot be discerned from faces that have been filtered with monochromatic noise, these unidentifiable famous faces still tend to receive higher familiarity ratings than similarly filtered non-famous faces. Experiment 1 investigated whether a similar face recognition without identification effect would occur among faces whose identification was hindered through the wearing of a surgical mask. Among a mixture of famous and non-famous faces wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Our results show that the impact of face masks was most prominent during famous face recognition and convincingly shows the effect of familiarity in both masked and unmasked condition while previous study [11] shows the opposite trend. However recent studies [19,20] shows effect on familiarity on masked face recognition which is in line with our results. A previous study [12] also found deterioration in performance for unfamiliar face compared to familiar face matching in cross-experimental comparisons.…”
Section: Effect Of Mask On Famous and Unfamiliar Face Recognitionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results show that the impact of face masks was most prominent during famous face recognition and convincingly shows the effect of familiarity in both masked and unmasked condition while previous study [11] shows the opposite trend. However recent studies [19,20] shows effect on familiarity on masked face recognition which is in line with our results. A previous study [12] also found deterioration in performance for unfamiliar face compared to familiar face matching in cross-experimental comparisons.…”
Section: Effect Of Mask On Famous and Unfamiliar Face Recognitionsupporting
confidence: 93%
“…However in studies showing familiarity effect using face mask including the current study, the task was more challenging. We use a 2-back test while [20] uses a recognition without identification paradigm and in [19], short-term memory for famous and unfamiliar identities in masked conditions were used. Participants identify the two faces within the same trial in matching tasks whereas in face memory tasks including ours, the participants use stored representation of faces shown previously to compare with the test image.…”
Section: Effect Of Mask On Famous and Unfamiliar Face Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this aim, in this thematic series, the detrimental effects of masks were investigated in children (Stajduhar & Freud, 2022 ) and in adults with Autistic Spectrum Disorder (Tso et al, 2022 ). Despite the detrimental effect of masks on famous face identification (Wong & Estudillo, 2022 ) familiarity-detection could still occur (Carlow et al, 2022 ). Research showed that it was harder to remember not only the identity of unfamiliar faces but whether or not that unfamiliar face wore a mask (Kollenda & de Haas, 2022 ) .…”
mentioning
confidence: 99%
“…This is perhaps a good candidate mechanism for transitioning attentional focus from being outward-directed to more inward-directed, and possibly for sending the hippocampus from a primarily encoding-focused mode to a retrieval-focused mode. Recent findings support this idea; two recent studies showed that people generate incorrect candidate bits of information (a possible indicator of retrieval search effort) more often when detecting familiarity with something (Carlaw, Huebert, McNeely-White, Rhodes, & Cleary, 2022;McNeely-White, 2022). Another recent study showed that systematically increasing a cue's perceived familiarity level during retrieval failure led to a corresponding increase in false recollective experience (another possible indicator of retrieval search effort; .…”
Section: What Flips Attention?mentioning
confidence: 95%